2018
DOI: 10.37134/saecj.vol7.1.2018
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers’ training and attitudes towards multicultural education in Malaysia

Abstract: Multicultural education is crucial in promoting cross-cultural understanding, recognition, and celebration of diversity in Malaysia-one of the most culturally diverse countries in the world. Preschool teachers play central roles in laying the foundation for cultural acceptance and positive racial interaction during early childhood. This study aims to explore Malaysian preschool teachers' training and attitudes towards multicultural education. A quantitative questionnaire survey approach was used to gather the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The teachers' lack of knowledge about multicultural education and their lack of knowledge of the concept of multicultural education and its components make us think that they cannot apply cultural arrangements and multicultural education activities in the classroom consciously and within a certain plan. So much so that Abdullah & Abdullah (2018) in their study in which they investigated teachers' attitudes towards multicultural education; They concluded that two-thirds of the teachers misunderstood the concept of multiculturalism, and therefore there were differences in their attitudes towards multicultural education.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…The teachers' lack of knowledge about multicultural education and their lack of knowledge of the concept of multicultural education and its components make us think that they cannot apply cultural arrangements and multicultural education activities in the classroom consciously and within a certain plan. So much so that Abdullah & Abdullah (2018) in their study in which they investigated teachers' attitudes towards multicultural education; They concluded that two-thirds of the teachers misunderstood the concept of multiculturalism, and therefore there were differences in their attitudes towards multicultural education.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…ESL teachers will benefit more from understanding methods to teach worldwide issues, managing stereotypes, multicultural issues, and conflicts. Abdullah and Abdullah (2018) and Chong and Yamat (2021) agreed that critical issues, including managing stereotypes, biases, and discriminatory behavior among students, need to be addressed in ESL education due to the inclusion of global topics in the CEFR-aligned syllabus. Understanding the topics in-depth and addressing more local and global issues in ESL lessons are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…They can effectively work in diverse classrooms and school environments ( Salzer and Roczen, 2018 ; Diveki, 2020 ; Yaccob et al, 2021 ). It is significant in the Malaysian ESL context since Malaysia is considered one of the most heterogeneous countries worldwide ( Abdullah and Abdullah, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Living in a multicultural society, every pupil comes from different backgrounds in terms of language and religion. A finding reveals that teachers' knowledge and attitude towards multicultural education in our country should be paid more attention to ameliorate the situation (Abdullah & Abdullah, 2018). It explains that the teaching process could be sophisticated when every pupil has their own different mother tongues in acquiring vocabulary.…”
Section: Barriers Of Vocabulary Teachingmentioning
confidence: 99%